Gospel truth. - Hyrynsalmi Big Band; Näyhä, Maria; Oikarinen, Taavetti; Haverinen, Antti; Matikainen, Minka; Heikkinen, Olli; Oikarinen, Matti, noin 1957- ([Kustannuspaikka tuntematon] : Musiikkiverstas, 1993)
8 kappaletta.
Kestoajat tarkistettu kuuntelemalla.
Hyrynsalmi Big Band: Maria Näyhä (lauluääni), Taavetti Oikarinen (alttosaksofoni), Antti Haverinen (alttosaksofoni), Minka Matikainen (tenorisaksofoni), Olli Heikkinen (baritonisaksofoni), Konsta Sievänen (tp), Teemu Ruohonen (tp), Tuomas Karjalainen (tp), Jussi Heikkinen (tp), Reima Sievänen (g), Minna Hiltunen (g), Eeva-Lotta Matikainen (b), Iida-Maria Oikarinen (p), Sami Seppänen (p), Oskari Oikarinen (perc), Markus Malin (dr, vib).
Äänitys: Studio Musiikkiverstas 1993.
Keywords: gospelmusiikki